Entre conversas, andarilhagens e camaradagens cotidianas: uma etnografia das invenções e resistências no campo das drogas - Silva, Leandro Roque da (Universidade Federal do Rio Grande do Norte, 2024)
The field of drugs is made up of an extensive set of practices, discourses, laws and norms that, aligned with moralistic pressure, serve as a substrate for drawing up legal guidelines made up of ethnic and ideological prejudices. Against this backdrop, the thesis deals with research that sought to follow, from the perspective of individual lives, forms of resistance that oppose prohibitionist policies on a daily basis in the context of north-eastern Brazil. Using the ethnographic method, three time periods were constructed as a resource for immersion in the field, which we call ethnographic wanderings, wall-to-wall conversations and slipper-to-wall conversations. Based on the narratives heard throughout the research, we constructed analyses based on three elements that emerged in these meetings: I) relationships between harmful drug use and the traumatic situations experienced and narrated by the participants; II) problematisation of how to witness and credit these narratives in the face of these bodies and desires seen as "deviant" in a prohibitionist society; and III) possible ways out as resistance in the face of everyday practices in relations with the territories accessed. In the early days of the research, in the surroundings of a CAPS AD III in a city in Paraíba, it was possible to compose a set of images and unique readings of the situations experienced in the territory, highlighting intersubjective, socioinstitutional and spatial relations. The analyses highlighted the importance of approaching everyday life in order to promote care and dialogue around trauma from a social and political perspective, together with the reflection on denial proposed by Ferenczi, in order to see that these subjective expressions that have been narrated become invisible, inaudible and untouched in the context of prohibition. However, as an alternative to this discrediting, Deleuze and Guattari proposed a discussion of the concept of war machines, making it possible to build places of resistance to the universalisations imposed by a colonialist and prohibitionist society through the creation of inventive lines of escape. And, finally, we brought the analysis of territories together with their constituent elements of subjectivity, as proposed by Deleuze and Guattari, so that, with Michel de Certeau, he could highlight the importance of everyday life in the construction of tactics in the face of situations of oppression. In this way, the analyzes woven here propose to us a field of microrevolutions that, despite coloniality and prohibitionism in social life and the absence of a State apparatus that protects and affirms lives, highlighted these partners as singular creators of their possibilities of life in its inventive and collective arrangements.
Keywords: Drogas psicotrópicas; Etnografia; Saúde mental; Trauma social; Práticas de resistência; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA